Hydrodynamic cavitation : devices, design and applications /: devices, design and applications. (2022) - Ranade, Vivek V; Bhandari, Vinay M; Nagarajan, Sanjay; Sarvothaman, Varaha P; Simpson, Alister A
No abstract available